Phonological Challenges and Error Patterns in English Consonant Production by Indonesian Learners: A Literature Review - Jauharah Jilan Situmorang; Yani Lubis; Rahma Fitri Yani Lubis (Jurnal Pendidikan dan Sastra Inggris, 2023)
This study aims to provide insights into the specific difficulties encountered by Indonesian learners. This study used literature review to explore the phonological challenges and error patterns faced by Indonesian learners in English consonant production. The findings reveal that Indonesian learners often make substitution errors, replacing English consonants with sounds from their native language that are more familiar to them. Additionally, voicing errors, difficulties with consonant clusters, struggles with fricative consonants, and challenges related to stress and rhythm patterns are identified as common issues. These errors and difficulties are influenced by the phonetic patterns and structures of the Indonesian language.